The Influence Comparison Of Steeping Green Tea Dregs (Camelia Sinensis (L.) Kuntze) And Steeping Rosella Tea Dregs (Hibiscus Sabdariffa Linn) As Denture Cleaner Towards Candida Albicans Growth - Aida Fameilia; Dewi Kristiana; R. Rahardyan Parnaadji (Jurnal Kesehatan Gigi, 2022)
Continuous use of dentures can hinder the cleaning process by the tongue and saliva, resulting in denture stomatitis. The main factor that causes denture stomatitis is the presence of Candida albicans. Green tea dregs and rosella tea dregs still contain compounds that have antifungal properties. Based on previous research, it was stated that green tea waste still contained polyphenols, flavonoids, gallic acid, catechins, EGCG, as well as rosella pulp also contained anthocyanins and phenolics. The presence of the following ingredients means that each infusion can reduce the amount of C. albicans growth. This research is a laboratory experimental study with 54 samples divided into 9 groups. The research group consisted of soaking samples of acrylic resin contaminated with C. albicans for 7 hours in the control group (sterile distilled water) and the treatment group, namely steeping green tea dregs with concentrations of 25%, 50%, 75%, 100% and rosella tea dregs steeping 25%, 50%, 75%, 100% which were then tested by spectrophotometer to see the absorbance of C. albicans. The data obtained were analyzed by ANOVA showing p0.005 so that the LSD test continued, it could be seen that there were significant differences between each treatment group and the control group, which means that the steeping of green tea dregs and the steeping of rosella tea dregs at concentrations of 25%, 50%, 75%, 100% affected the growth of C. albicans on heat-cured acrylic resin, but between groups of various concentrations of steeping tea dregs did not show a significant effect.